ANALISIS EARNING PER SHARE (EPS) DAN DEVIDEND PER SHARE (DPS) BERPENGARUH TERHADAP HARGA SAHAM Studi Kasus Pada : BANK RAKYAT INDONESIA Persero, Tbk Tahun Periode 2006-2017 - Eman Singgih (LPPM UNIVERSITAS INSAN PEMBANGUNAN INDONESIA, 2019)
Abstract Equity market or equity participation in a company still promises great growth and income to potential long-term investors so that they can get the same results as the economies of developed and developing countries. To know this, potential investors must be able to understand the company's financial performance . Earnings per share EPS is one of the most important financial instruments to be able to know the income of shares owned, as well as the dividend per share DPS which can describe the dividends received by shareholders. The value of the stock which is getting better will illustrate the company's performance getting better and vice versa, this can attract investors to buy company shares. So that it can increase the company's working capital including the national banking industry in the case of BRI Bank as the Red Plate Bank. Both EPS and DPS variables have a strong impact both simultaneously and partially, while DPS has a very large effect compared to EPS